Estimation of Glomerular Filtration Rate in Diabetic Subjects - Rigalleau, Vincent; Lasseur, Catherine; Perlemoine, Caroline; Barthe, Nicole; Raffaitin, C.; Liu, Chung; Chauveau, Phillipe; Baillet-Blanco, Laurence; Beauvieux, Marie-Christine; Combe, C.; Gin, Henri (Diabetes care, 2005)
Estimation of Glomerular Filtration Rate in Diabetic Subjects Cockcroft formula or Modification of Diet in Renal Disease study equation? Vincent Rigalleau , MD, PHD 1 , Catherine Lasseur , MD 2 , Caroline Perlemoine , MD 1 , Nicole Barthe , PD 3 , C. Raffaitin , MD 1 , Chung Liu , MD 1 , Phillipe Chauveau , MD 2 , Laurence Baillet-Blanco , MD 1 , Marie-Christine Beauvieux , PD 1 , C. Combe , MD, PHD 2 and Henri Gin , MD, PHD 1 1 Department of Nutrition and Diabetes, Hôpital Haut-Lévêque, Pessac, France 2 Department of Nephrology, University Victor Segalen Bordeaux II, Bordeaux, France 3 Department of Nuclear Medicine, University Victor Segalen Bordeaux II, Bordeaux, France Address correspondence and reprint requests to Vincent Rigalleau, Nutrition-Diabétologie, Hôpital Haut-Lévêque, Avenue de Magellan, 33600 Pessac, France. E-mail: vincent.rigalleauatwanadoo.fr Abstract OBJECTIVE —The Cockcroft-Gault formula is recommended for the evaluation of renal function in diabetic patients. The more recent Modification of Diet in Renal Disease (MDRD) study equation seems more accurate, but it has not been validated in diabetic patients. This study compares the two methods. RESEARCH DESIGN AND METHODS —In 160 diabetic patients, we compared the Cockcroft-Gault formula and MDRD equation estimations to glomerular filtration rates (GFRs) measured by an isotopic method ( 51 Cr-EDTA) by correlation studies and a Bland-Altman procedure. Their accuracy for the diagnosis of moderately (GFR <60 ml · min −1 · 1.73 m −2 ) or severely (GFR <30 ml · min −1 · 1.73 m −2 ) impaired renal function were compared with receiver operating characteristic (ROC) curves. RESULTS —Both the Cockcroft-Gault formula ( r = 0.74; P < 0.0001) and MDRD equation ( r = 0.81; P < 0.0001) were well correlated with isotopic GFR. The Bland-Altman procedure revealed a bias for the MDRD equation, which was not the case for the Cockcroft-Gault formula. Analysis of ROC curves showed that the MDRD equation had a better maximal accuracy for the diagnosis of moderate (areas under the curve [AUCs] 0.868 for the Cockcroft-Gault formula and 0.927 for the MDRD equation; P = 0.012) and severe renal failure (AUC 0.883 for the Cockcroft-Gault formula and 0.962 for the MDRD equation; P = 0.0001). In the 87 patients with renal insufficiency, the MDRD equation estimation was better correlated with isotopic GFR (Cockcroft-Gault formula r = 0.57; the MDRD equation r = 0.78; P < 0.01), and it was not biased as evaluated by the Bland-Altman procedure. CONCLUSIONS —Although both equations have imperfections, the MDRD equation is more accurate for the diagnosis and stratification of renal failure in diabetic patients. AUC, area under the curve ESRD, end-stage renal disease GFR, glomerular filtration rate MDRD, Modification of Diet in Renal Disease ROC, receiver operating characteristic Footnotes A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Accepted December 20, 2004. Received September 12, 2004. DIABETES CARE